The Way of the Cross as the Origin of the Devotion to Jesus of Nazareth in Andalusian Holy Week: A Historical, Anthropological, and Theological Approach - Romero Pérez, José Manuel (Razón y fe, 2026)
This study examines the origin and consolidation of the devotion to Jesus of Nazareth in Andalusian Holy Week from a threefold perspective: historical, theological, and anthropological. The main hypothesis argues that the root of this devotion lies in the practice of the Stations of the Cross, introduced in the West by Blessed Álvaro of Córdoba in the fifteenth century. The article analyzes how penitential brotherhoods became a privileged channel of sociability and popular religiosity, reaching their fullness in the Baroque period and within the normative framework of the Council of Trent. The image of Jesus carrying the cross thus emerges as the symbolic center of Andalusian religiosity, synthesizing faith, culture, and communal identity. The interdisciplinary approach adopted here makes it possible to assess the originality of Andalusian popular religiosity and opens the way for a critical comparison with other peninsular and Mediterranean traditions.
Keywords: Jesus of Nazareth; Stations of the Cross; Andalusia; Holy Week; brotherhoods; popular religiosity; Baroque; Council of Trent